Experiments in plant tissue culture - Dodds, John H.; Roberts, Lorin W. (Cambridge; New York : Cambridge University Press, 1985)
The third edition of Experiments in Plant Tissue Culture makes available new and updated information that has resulted from recent advances in the applications of plant tissue culture techniques to agriculture and industry. This laboratory text features an enlarged section on terminology and definitions as well as additional information on equipment and facilities.
This comprehensive text takes the reader through a graded series of experimental protocols and also provides a preliminary review of each topic. After an introductory historical background, there are discussions of a plant tissue culture laboratory, aseptic techniques, and nutritional components of media.
Subsequent chapters are devoted to callus induction, organ formation, cell suspensions, somatic embryogenesis, root cultures, micropropagation, anther and pollen cultures, xylem cell differentiation, isolation and fusion of protoplasts, storage of genetic resources, secondary metabolite production, and quantitation of procedures. A glossary of terms, a list of commercial sources of supplies, and a table of media formulations are included.
. This book offers all the basic experimental methods for the major research areas of plant tissue culture, and will be invaluable to undergraduates and research investigators in the plant sciences. It will also be useful to researchers in related areas such as forestry, agronomy, and horticulture, and to those in commercial houses and pharmaceutical companies interested in acquiring the laboratory techniques.
Foreword / J. Heslop-Harrison -- I. Background information. 1. Culture of plant cells, tissues, and organs. 2. Laboratory facilities. 3. Aseptic techniques. 4. Media composition and preparation -- II. Experimental: Callus and callus-derived systems. 5. Initiation and maintenance of callus. 6. Organogenesis. 7. Cell suspensions. 8. Somatic embryogenesis -- III. Experimental: Culture of organs and organized systems. 9. Isolated roots. 10. Micropropagation by bud proliferation. 11. Anther and pollen cultures -- IV. Experimental: Isolated cells. 12. Transdifferentiation of parenchyma cells to tracheary elements. 13. Isolation and culture of protoplasts. 14. Protoplast fusion and somatic hybridization -- V. Supplementary topics. 15. Cryopreservation of germplasm. 16. Production of secondary metabolites. 17. Quantitation of procedures.
Includes bibliographical references and indexes.
Keywords: Plant tissue culture -- Experiments